Bacterial Toxin‐Triggered Release of Antibiotics from Capsosomes Protects a Fly Model from Lethal Methicillin‐Resistant Staphylococcus aureus (MRSA) Infection. Issue 14 (11th May 2022) - Tonkin, Renée L.; Klöckner, Anna; Najer, Adrian; Simoes da Silva, Carolina J.; Echalier, Cécile; Dionne, Marc S.; Edwards, Andrew M.; Stevens, Molly M.
Abstract: Antibiotic resistance is a severe global health threat and hence demands rapid action to develop novel therapies, including microscale drug delivery systems. Herein, a hierarchical microparticle system is developed to achieve bacteria‐activated single‐ and dual‐antibiotic drug delivery for preventing methicillin‐resistant Staphylococcus aureus (MRSA) bacterial infections. The designed system is based on a capsosome structure, which consists of a mesoporous silica microparticle coated in alternating layers of oppositely charged polymers and antibiotic‐loaded liposomes. The capsosomes are engineered and shown to release their drug payloads in the presence of MRSA toxins controlled by the Agr quorum sensing system. MRSA‐activated single drug delivery of vancomycin and synergistic dual delivery of vancomycin together with an antibacterial peptide successfully kills MRSA in vitro. The capability of capsosomes to selectively deliver their cargo in the presence of bacteria, producing a bactericidal effect to protect the host organism, is confirmed in vivo using a Drosophila melanogaster MRSA infection model. Thus, the capsosomes serve as a versatile multidrug, subcompartmentalized microparticle system for preventing antibiotic‐resistant bacterial infections, with potential applications to protect wounds or medical device implants from infections. Abstract : Bacterial toxin‐activated capsosomes are employed for single and synergistic dual delivery of antimicrobial drugs for the prevention of methicillin‐resistant Staphylococcus aureus ( S. aureus ) (MRSA) infections. The toxin‐triggered release mechanism is characterized and the bactericidal efficacy of the antibiotic‐loaded capsosomes is demonstrated in vitro and in an in vivo fly infection model of lethal MRSA infection.